Solubility of ethyl ester of 2-cyano-3-[5-(4-methylphenyl)-2-furan] acrylic acid in organic solvents - Kos, R. V.; Sobechko, I. B.; Kochubey, V. V.; Vahula, A. R.; Sergeev, V. V. (Видавництво Львівської політехніки, 2016)
The solubility of ethyl ester of 2-cyano-3-[5-(4-methylphenyl)-2-furan] acrylic acid in acetonitrile, benzene, 2-propanol and ethyl acetate at temperatures 299.0-333.0 C was determined. From the temperature dependence of the solubility of ethyl ester of 2-cyano-3-[5- (4-methylphenyl)-2-furan] acrylic acid enthalpy and entropy of dissolution in investigated solvents were calculated. According to differential thermal analysis the enthalpy and entropy of melting of ethyl ester of 2-cyano-3-[5-(4-methylphenyl)-2-furan] acrylic acid were identified and adjusted to 298K. The influence of solvents polarity on the solubility and magnitude of enthalpy and entropy of mixing at 298K was established. Визначено розчинність етилового естеру 2-ціано-3-[5-(4-метилфеніл)-2-фуран] акрилової кислоти в ацетонітрилі, бензолі, пропанолі-2 та етилацетаті в інтервалі температур 299,0-333,0 К. За температурною залежністю розчинності етилового естеру 2-ціано-3-[5-(4-метилфеніл)-2-фуран] акрилової кислоти розраховано ентальпію та ентропію розчинення в досліджених розчинниках. За даними диференційно-термічного аналізу визначено ентальпію і ентропію плавлення етилового естеру 2-ціано-3-[5-(4-метилфеніл)-2-фуран] акрилової кислоти та перераховано їх на 298К. Встановлено вплив полярності розчинників на розчинність та величини ентальпії і ентропії змішування при 298 К.
Розчинність етилового естеру 2-ціано-3-[5-(4-метилфеніл)-2-фуранакрилові кислоти в органічних розчинниках
Keywords: enthalpy of dissolution; entropy of dissolution; enthalpy mixing; entropy melting; differential thermal analysis; ethyl ester of 2-cyano-3-[5-4-methylphenyl)-2-furan] acrylic acid; ентальпія розчинення; ентропія розчинення; ентальпія змішування; ентропія плавлення; диференційний термічний аналіз; етиловий естер 2-ціано-3-[5-4-метилфеніл)-2-фуран] акрилової кислоти